Cellulitis: A Study of Drug Use Evaluation in a Tertiary Care Teaching Hospital - Patil, Shrishailgouda S.; S, Sreekanth.; Baby, Berlin; Sravani, Adireddy; Geethika, Grandhe; Hiremath, Doddayya (Indian Journal of Pharmacy Practice)
Background: Inappropriate use of drugs especially antibiotics, in the treatment of cellulitis results in therapeutic failure and recurrence of cellulitis. Drug use evaluation is a performance improvement method that focuses on evaluation and improvement of drug use processes to achieve optimal therapeutic outcomes. Objectives: The present work deals with the drug use evaluation in cellulitis with an aim to improve therapeutic outcomes of the disease. Methodology: The prospective observational study on the drug utilization evaluation in cellulitis was carried out on a total of 67 cellulitis in-patients from the departments of medicine, surgery, orthopaedics of Navodaya Medical College Hospital and Research Centre, Raichur. Relevant information was recorded in a structured proforma & data was evaluated. The drugs used in the treatment were evaluated by comparing with by using CREST (Clinical Resource Efficiency Support Team guidelines, developed by Central Medical Advisory Committee, Ireland) guidelines. Results: Out of 67 patients 53 patients were diagnosed with Class 2 cellulitis, 13 patients were Class 3 cellulitis and only 1 patient was Class 4 cellulitis (Class 1 cellulitis patients are treated on out-patient basis and hence not included in the study). The rank order of antibiotics prescribed in the treatment was as follows: Cephalosporins>aminoglycosides>penicillins>macrolides>fluoroquinolones. Conclusion: An overall deviation in 28.3% patients as been observed in the line of treatment with respect to antibiotics use as per CREST guidelines. Further, deviation was also observed in prophylactic antibiotics prescribed to prevent the recurrence of cellulitis. The study also revealed the lack of awareness in the cellulitis patients regarding the disease, its recurrence and prevention. Thus, the study intensifies the need to create the awareness among the physicians regarding the appropriate use of antibiotics and in patients to prevent its occurrence and recurrence.
Keywords: Cellulitis; Prospective observational study; Drug use evaluation; Antibiotics; CREST guidelines.